The economics of immigration and social diversity - Polachek, S. W.; Chiswick, Carmel U.; Rapoport, Hillel (Emerald, 2006)
This volume is a collection of papers dedicated to the memory of the late Tikva Lecker. Professor Lecker's many interests included topics in labor economics, women and the economy, the economics of Judaism, the economics of migration and every aspect of the economic experience of immigrants and their descendants. Each chapter in this volume honors the memory of Professor Lecker by presenting research on a topic in which she was especially interested. The Research in Labor Economics series was started in 1977. Each volume consists of a collection of refereed research papers written by top economists. Recent volumes have hosted papers from D. Acemoglu, J.D. Angrist, D. Card, H. Farber, A. Kreuger, E. Lazear, G. Field, and J. Mincer, among others.
Keywords: Labor economics.; Labor supply -- United States.; elektronické knihy; electronic books